How does social support influence tourist-oriented citizenship behavior? A self-determination theory perspective - Li, Ruyou; Shi, Zhangyu (Frontiers in Psychology, 2022)
As a driver of tourist-oriented citizenship behavior (TOCB), the effect of social support has not been thoroughly investigated. Grounded in a framework integrating the stimulus-organism-response model and self-determination theory, this study investigates how social support influences TOCB through the sense of self-determination. Structural equation modeling is used to analyze the survey data collected from 377 tourists in China. It is found that social support (information and emotional support) have a remarkably positive impact on the sense of self-determination (perceived autonomy, competence, and relatedness) which have an intermediary role in the relationship between social support and TOCB. This study provides empirical evidence for the marketing strategies of tourism destinations and enterprises.